2004
DOI: 10.1172/jci22922
|View full text |Cite
|
Sign up to set email alerts
|

Lentivector-mediated SMN replacement in a mouse model of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a frequent recessive autosomal disorder. It is caused by mutations or deletion of the telomeric copy of the survival motor neuron (SMN) gene, leading to depletion in SMN protein levels. The treatment rationale for SMA is to halt or delay the degeneration of motor neurons, but to date there are no effective drug treatments for this disease. We have previously demonstrated that pseudotyping of the nonprimate equine infectious anemia virus (using the lentivector gene transfer syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(75 citation statements)
references
References 27 publications
2
70
1
2
Order By: Relevance
“…The lentiviral vector for delivery of hPGC-1α in our study was well tolerated, did not trigger adverse effects, and allowed sustained expression of the transgene for months. Successful proof-of-principle studies of gene therapy using similarly pseudotyped lentiviral vectors have been demonstrated in animal models of ALS (34,35), spinal muscular atrophy (36), and spinal nerve injury (37). In addition, we have developed and tested a similar vector for dopamine replacement therapy in late stage Parkinson's disease patients in a phase I/II clinical trial, showing long-term expression and improved motor behavior in treated patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…The lentiviral vector for delivery of hPGC-1α in our study was well tolerated, did not trigger adverse effects, and allowed sustained expression of the transgene for months. Successful proof-of-principle studies of gene therapy using similarly pseudotyped lentiviral vectors have been demonstrated in animal models of ALS (34,35), spinal muscular atrophy (36), and spinal nerve injury (37). In addition, we have developed and tested a similar vector for dopamine replacement therapy in late stage Parkinson's disease patients in a phase I/II clinical trial, showing long-term expression and improved motor behavior in treated patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…This will require appropriate transfer vectors. Some initial success was obtained by Azzouz, Mazarakis and coworkers by using lentiviral vectors, 152,153 but recent results indicate that self-complementary AAV9 vectors can efficiently transduce motoneurons, when injected into presumably also not concentrated in the nucleus, underlining the importance of a snRNA backbone for RNA stability and nucleoplasmic accumulation.…”
Section: Smn2 Exon 7 Inclusionmentioning
confidence: 99%
“…Although EIAV-based vectors are about 10-fold less efficient in several human cell lines than HIV-1 based vectors (Ikeda et al, 2002), they have demonstrated good efficiency for treatment of neuromuscular pathologies in animal models (Azzouz et al, 2004;Yip et al, 2006). In addition, they are able to transduce human HSCs (Siapati et al, 2005) and are very efficient in vivo.…”
Section: Equine Infectious Anaemia Virus (Eiav)-based Vectorsmentioning
confidence: 99%